Adapted beamformer of transceiver antenna by composite materials for radiology system. (2021) - Sivaraj, S.; Nagaraju, V.; Anbarasan, S.; Senthilkumar, R.; Sakthisudhan, K.
Abstract: A radiology clinical system has developed from Adapted Minimum Variance Distortionless Response (MVDR) algorithm is presented in this research. The proposed system has an equivalent Microwave Imaging (MI) system. It consists of the composite materials with wearable transceiver antenna. The biological components of the breast organ has prepared using composite materials, which is wrapped transceiver antenna connected to the Agilent Microwave Analyzer (N9917A). Angle of arrival signals from transmitter and Received Signal Strength (RSS) have gathered by Microwave Analyzer. The intensity of signals had estimated by Power Spectral Density (PSD). Finally, 2D images have extracted from the proposed algorithm. Thus, these images have achieved from different kinds of resolution stages. Furthermore, these diagnosed images have justified with composite materials.